Interactive effect of phenylalanine with duration of diabetes on the risk of small vessel disease in Chinese patients with T2DM - Zheng, Jun; Zhang, Wei; Miao, Yu-Yang; Li, Xue-Rui; Luo, Wei-Ming; Yang, Xi-Lin; Fang, Zhong-Ze; Zhang, Qiang (Frontiers in Endocrinology, 2025)
Aims Few prior studies have explored the relationship between phenylalanine and diabetic small vessel disease (SVD) in patients with different durations of type 2 diabetes mellitus(T2DM). Our study aimed to explore whether phenylalanine is associated with the risk of SVD and to further explore whether phenylalanine interacted with the duration of T2DM to alter the risk of SVD. Materials and methods A total of 1,032 T2DM patients were enrolled using the Liaoning Medical University First Affiliated Hospital (LMUFAH) system. SVD was defined as patients with diabetic nephropathy (DN) or diabetic retinopathy (DR) alone, or both. Serum amino acids were measured by mass spectrometry (MS) technology. A binary logistic regression model was used to examine associations of phenylalanine with SVD risk. Restricted cubic spline (RCS) regression was used to draw the odds ratio curves of plasma phenylalanine for SVD. Additive interaction analysis was employed to test the interaction of low phenylalanine with a long duration of T2DM for SVD. Results Among the 1,032 T2DM patients, 286 (27.7%) had SVD. Phenylalanine <42μmol/L was associated with a markedly increased risk of SVD (OR 1.76, 95%CI 1.23 to 2.51), which was enhanced by a duration of T2DM of ≥5 years to 4.83 (95%CI 2.97-7.87) with significant additive interactions. The inclusion of phenylalanine and duration of T2DM into a traditional risk factor model substantially increased the area under the receiver operating characteristic curve from 0.67 to 0.71 (95% CI 0.70 to 0.75) (P <0.05). Conclusions In Chinese patients with T2DM, phenylalanine <42μmol/L was associated with an increased risk of SVD, which was further amplified by a duration of T2DM of ≥5 years.